Modeling susceptibility to drug-induced long QT with a panel of subject-specific induced pluripotent stem cells - Stillitano, Francesca; Hansen, Jens; Kong, Chi-Wing; Karakikes, Ioannis; Funck-Brentano, Christian; Geng, Lin; Scott, Stuart; Reynier, Stephan; Wu, Ma; Valogne, Yannick; Desseaux, Carole; Salem, Joe-Elie; et al. (eLife, 2017)
A large number of drugs can induce prolongation of cardiac repolarization and life-threatening cardiac arrhythmias. The prediction of this side effect is however challenging as it usually develops in some genetically predisposed individuals with normal cardiac repolarization at baseline. Here, we describe a platform based on a genetically diverse panel of induced pluripotent stem cells (iPSCs) that reproduces susceptibility to develop a cardiotoxic drug response. We generated iPSC-derived cardiomyocytes from patients presenting in vivo with extremely low or high changes in cardiac repolarization in response to a pharmacological challenge with sotalol. In vitro, the responses to sotalol were highly variable but strongly correlated to the inter-individual differences observed in vivo. Transcriptomic profiling identified dysregulation of genes ( DLG2, KCNE4, PTRF, HTR2C , CAMKV ) involved in downstream regulation of cardiac repolarization machinery as underlying high sensitivity to sotalol. Our findings offer novel insights for the development of iPSC-based screening assays for testing individual drug reactions. Common medications can disturb the electrical signals that cause the heart to beat, potentially resulting in sudden death. Many of the drugs that have these “cardiotoxic” effects were not designed to affect the heart, and include anti-allergenics and anti-vomiting drugs. In general, only a small proportion of individuals treated with these drugs will be at risk of fatal side effects; this risk variation is thought to be due to genetic differences. If these people could be reliably identified, the drugs could be used to treat others who will not develop cardiotoxic reactions, but it is difficult to predict the effect a drug will have on the beating of the heart. Stillitano, Hansen et al. have now investigated whether skin cells can be used to predict an individual’s likelihood of developing cardiotoxic side effects. Skin cells can be reprogrammed to form pluripotent stem cells, which have the ability to develop into any of the cell types in the adult body – including heart muscle cells. The effects of drugs could then be tested on these artificially created heart cells, yet it is not clear whether these effects would be the same as those seen in actual heart cells Stillitano, Hansen et al. created heart cells from skin samples collected from many different people and treated the cells with a drug that affects the rhythm of the heart. Some of the cells came from people whose heart rhythm is strongly affected by the drug, and others came from people whose heart rhythm is barely altered. The response of the lab-grown cells was closely related to whether the cells came from a person who was susceptible to the effects of the drug. Further investigation revealed that the genes that are important for maintaining a regular heartbeat differ in people who experience strong cardiotoxic side effects from those that do not. Overall, the results presented by Stillitano, Hansen et al. support the idea that induced pluripotent stem cells could be used to predict an individual’s risk of developing cardiotoxic reactions. Further work is now needed to develop this approach.